AKTIVITAS ANTIBAKTERI DAN ANTIOKSIDAN EKSTRAK IXORA CUMINGIANA - Kartika Dyah Palupi; Praptiwi Praptiwi; Dewi Wulansari; Andria Agusta (BERITA BIOLOGI, 2020)
Plants from Ixora genus exhibit a variety of pharmacological activities including antioxidant, antibacterial, and antitumor activities. This plants may contain many interesting bioactive compounds, especially phenolics and terpenoids groups. Ixora cumingiana is one of the Ixora species whose pharmacological effect has not been explored comprehensively. This study aimed to evaluate the antibacterial and antioxidant activity of eight extracts from bark and leaf of I. cumingiana. The plant samples were successively extracted using n-hexane, dichloromethane, ethyl acetate and methanol. The antibacterial evaluation was carried out against Staphylococcus aureus and the antioxidant activity was evaluated using a radical scavenging assay against 1,1-diphenyl-2-picrylhydrazyl (DPPH). Initial activity screening was performed using thin layer chromatography-bioautography followed by the determination of minimum inhibitory concentration (MIC) and the determination of antioxidant activity index (AAI) using microdilution technique. The dichloromethane extract of the bark as well as the n-hexane and dichloromethane extract of the leaf of I. cumingiana exhibited moderate antibacterial effect with MIC value of 128, 128, and 256 µg/ml, respectively. The methanol extract from the bark displayed a strong antioxidant activity (AAI = 1.5±0.13) and possessed the highest total phenolic content (43±0.91 mg AGE/ g extract). These experimental results showed that I. cumingiana is potential to be developed as an antioxidant agent rather than as an antibacterial agent.